Tandem-L: A Mission for Monitoring Earth System Dynamics with High Resolution SAR Interferometry - Krieger, Gerhard; Hajnsek, I.; Papathanassiou, K.; Eineder, M.; Younis, M.; De Zan, F.; Lopez-Dekker, P.; Huber, S.; Werner, M.; Prats, P.; Fiedler, H.; Freeman, A.; et al. (European Conference on Synthetic Aperture Radar (EUSAR), 2010)
Tandem-L is a proposal for an innovative interferometric and polarimetric radar mission that enables the systematic monitoring of dynamic processes on the Earth surface. Important mission objectives are global forest height and biomass inventories, large scale measurements of millimetric displacements due to tectonic shifts, and systematic observations of glacier movements. The innovative mission concept and the high data acquisition capacity of Tandem-L provide a unique data source to observe, analyze and quantify the dynamics of a wide range of mutually interacting processes in the bio-, litho-, hydro- and cryosphere. By this, Tandem-L will be an essential step to advance our understanding of the Earth system and its intricate dynamics.
DLR Import::2019-04-03